(untitled) (Asean Journal of Engineering Education, 2023)
"TRIZ - Systematic Innovation in Manufacturing" is a comprehensive guide unveiling the transformative potential of the Theory of Inventive Problem Solving (TRIZ) within manufacturing contexts. This insightful book delves into the core principles of TRIZ, equipping professionals and engineers with a structured approach to tackle intricate challenges and drive innovation. Offering a blend of theory and practical applications, the book elucidates TRIZ methodologies through illustrative case studies, examples, and exercises tailored to the manufacturing sector. It navigates through inventive principles and contradiction resolution strategies, showcasing TRIZ’s efficacy in optimizing processes, enhancing designs, and overcoming operational bottlenecks. While potentially challenging for those new to TRIZ, this resource serves as an invaluable asset for professionals seeking inventive solutions and systematic problem-solving approaches within manufacturing environments.